Relationship between body composition and bone mass in normal-weight and overweight adolescents - Bim M.A.* (2022)
© 2022 Bim et al.Adolescence is a period characterized by large accumulation of bone mass. Body composition is an important determinant of bone mass. This study aimed to assess the relationship of bone mass with lean mass (LM) and fat mass (FM) in normal-weight and overweight adolescents with consideration of sex, sexual maturation and physical activity covariates. A total of 118 adolescents (60 girls and 58 boys) aged between 10 and 14 years participated in the study. Individuals were classified as normal weight or overweight according to body mass index. Bone mineral density (BMD), bone mineral content (BMC), LM, and FM were measured by dual-energy X-ray absorptiometry. In normal-weight adolescents, LM (β=0:725, p < 0.001) and FM (β=0:185, p D 0.019) were associated with lumbar spine BMC, whereas in overweight adolescents only LM (β= 0:736, p < 0.001) was associated with lumbar spine BMC. Furthermore, in the normal-weight group, FM and LM were associated with total body less head BMD (LM, β =0:792, p < 0.001; FM, β =0:257, p = 0.007) and lumbar spine BMD (LM, β =0:553, p < 0.001; FM, β =0:199, p < 0.035). In the overweight group, only LM was associated with total body less head BMD (β=0:682, p < 0.001) and lumbar spine BMD(β =0:528, p<0.001).LMwas the main predictor of bone mass in normal-weight and overweight adolescents. FM was associated with bone mass in normal-weight adolescents only.LMmay be considered an important and useful marker in adolescents, when investigating bone health in this population. Activities that promote LM gain to reduce the risk of bone fractures and diseases in adulthood are recommended.